A method for preparing a nickel hydroxide electrode by doctor blade coating
Patent Information
- Application Number
- CN202611044513.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]本发明提供一种氢氧化镍电极的刮刀涂覆制备方法,以解决现有泡沫镍浸渍法中活性物质负载量和分布一致性不足、刮刀涂覆过程中浆料与泡沫镍基材匹配性不足的问题
[0014]与现有技术相比,本发明至少具有如下有益效果:本发明将泡沫镍预处理、氢氧化镍正极浆料制备、刮刀涂覆、多阶段干燥和碾压裁切组合成连续制备流程,使正极浆料进入泡沫镍孔隙并在泡沫镍表面形成厚度稳定的涂覆层,从而提高氢氧化镍电极的活性物质负载量和极片一致性;通过低温阶段和高温阶段组合干燥,减少溶剂快速挥发导致的涂层缺陷;通过后续碾压,形成厚度受控的电极结构,并增强活性物质与泡沫镍集流体之间的结合。
Smart Images

Figure CN122907604A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nickel-metal hydride battery electrode preparation technology, specifically to a method for preparing a nickel hydroxide electrode by blade coating. Background Technology
[0002] Nickel hydroxide electrode is the positive electrode structure in nickel-metal hydride battery. The loading, distribution uniformity, compaction state of the active material in the electrode, as well as the bonding state between the active material and the nickel foam current collector, will affect the battery's capacity, rate performance, and cycle life.
[0003] Current industrial-scale preparation processes commonly employ the nickel foam impregnation method. This method relies primarily on the capillary permeation of the slurry into the pores of the nickel foam to load the active material. While the process equipment is relatively simple, it suffers from several drawbacks when preparing high-load nickel hydroxide electrodes, including low active material loading, inconsistent loading in different areas of the electrode, insufficient filling within the nickel foam, and difficulty in controlling batch consistency. Furthermore, when the electrode structure is porous, active material is prone to detachment during subsequent cycles.
[0004] When applying the blade coating process to nickel-foamed nickel hydroxide electrodes, it is necessary to consider the three-dimensional porous structure of nickel foam, the high particle density and easy settling characteristics of nickel hydroxide, the degree of slurry penetration into the pores of nickel foam, and the thickness of the slurry remaining on the surface of nickel foam. If there is a lack of matching between the slurry formulation, coating thickness, blade linear speed, drying temperature, and rolling thickness, problems such as localized material accumulation, surface cracking, insufficient internal load, or unstable electrode thickness can easily occur.
[0005] Therefore, it is necessary to develop a preparation method for the combination of nickel hydroxide slurry and nickel foam current collector, which includes substrate pretreatment, slurry preparation, doctor blade coating, multi-stage drying, and rolling and cutting. Summary of the Invention
[0006] This invention provides a method for preparing nickel hydroxide electrodes by blade coating, which solves the problems of insufficient loading and distribution consistency of active materials and insufficient matching between slurry and nickel foam substrate in the existing nickel foam impregnation method.
[0007] The present invention adopts the following technical solution.
[0008] A method for preparing a nickel hydroxide electrode by scraper coating includes: sequentially performing surface pretreatment, drying, and cutting on a nickel foam substrate to obtain a nickel foam current collector; mixing a nickel-containing positive electrode mixed powder, a conductive agent, polyvinylidene fluoride, and N-methylpyrrolidone, and then dispersing and degassing the mixture to obtain a positive electrode slurry, wherein the nickel-containing positive electrode mixed powder includes nickel hydroxide, yttrium oxide, and a cobalt source compound; laying the nickel foam current collector flat and fixing it, placing the positive electrode slurry at one end of the nickel foam current collector, and using a scraper to move along the surface of the nickel foam current collector, so that the positive electrode slurry enters the pores of the nickel foam current collector and forms a wet film on the surface of the nickel foam current collector to obtain a coated electrode sheet; sequentially performing a first-stage drying and a second-stage drying on the coated electrode sheet to obtain a dried electrode sheet; and rolling and cutting the dried electrode sheet to obtain the nickel hydroxide electrode.
[0009] In one embodiment, the surface pretreatment includes ultrasonically cleaning the nickel foam substrate in a citric acid solution, followed by ultrasonic cleaning in acetone; after ultrasonic cleaning with the citric acid solution, the substrate is washed with water, and after ultrasonic cleaning with acetone, it is dried at 40°C to 80°C. The nickel foam substrate can be a nickel foam substrate with a thickness of 1 mm and a pore count of 110 PPI.
[0010] In one embodiment, nickel hydroxide, yttrium oxide, and a cobalt source compound are mixed in a mass ratio of 9.7 to 9.9: 0.01 to 0.04: 0.05 to 0.09 to form a nickel-containing cathode mixed powder. The cobalt source compound is cobalt(II) oxide or cobalt(II) hydroxide. Based on 100 parts by weight of the nickel-containing cathode mixed powder, the conductive agent is 0.01 to 5 parts by weight, and the polyvinylidene fluoride is 8 to 20 parts by weight.
[0011] In one embodiment, the conductive agent is selected from one or more of nickel powder, acetylene black, graphite powder and cobalt hydroxide; polyvinylidene fluoride is added as a polyvinylidene fluoride solution, wherein the mass fraction of the polyvinylidene fluoride solution is 5% to 15%, and the solvent of the polyvinylidene fluoride solution is N-methylpyrrolidone.
[0012] In one embodiment, the wet film thickness coated by the doctor blade is 10 μm to 200 μm, and the linear speed of the doctor blade coating is 0.3 m / min to 1.5 m / min; specifically, the wet film thickness is 150 μm, and the gap between the doctor blade and the nickel foam current collector is set according to the wet film thickness.
[0013] In one embodiment, the first stage of drying is carried out at a temperature of 70°C to 90°C for 2 to 3 hours; the second stage of drying is carried out at a temperature of 90°C to 110°C for 2 to 3 hours; and the drying air velocity is 0.1 m / s to 1 m / s. The thickness of the rolled electrode sheet is 0.65 mm to 0.85 mm.
[0014] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention combines the pretreatment of nickel foam, preparation of nickel hydroxide positive electrode slurry, doctor blade coating, multi-stage drying and rolling cutting into a continuous preparation process, so that the positive electrode slurry enters the pores of nickel foam and forms a coating layer with stable thickness on the surface of nickel foam, thereby improving the active material loading and electrode uniformity of nickel hydroxide electrode; by combining low temperature stage and high temperature stage drying, coating defects caused by rapid solvent evaporation are reduced; by subsequent rolling, an electrode structure with controlled thickness is formed, and the bonding between active material and nickel foam current collector is enhanced. Attached Figure Description
[0015] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 This is a cyclic voltammetry curve of the nickel hydroxide electrode prepared in Example 1 of the present invention.
[0016] Figure 2 This is a charge-discharge curve of the nickel hydroxide electrode prepared in Example 1 of the present invention. Detailed Implementation
[0017] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0018] Example 1 This embodiment provides a method for preparing a nickel hydroxide electrode using a scraper coating process, which proceeds in the following order: substrate pretreatment, slurry preparation, scraper coating, multi-stage drying, rolling and cutting, and performance testing. First, the nickel foam substrate is pretreated. A nickel foam substrate with a thickness of 1 mm and a pore size of 110 PPI is selected and cut into sheet-like substrates for easy cleaning and coating. The sheet-like substrates are ultrasonically cleaned in a citric acid solution, followed by rinsing with deionized water; subsequently, the sheet-like substrates are ultrasonically cleaned in acetone. The citric acid solution ultrasonic cleaning is used to remove oxides and inorganic contaminants from the surface of the nickel foam substrate, while the acetone ultrasonic cleaning is used to remove oil, organic residues, and adsorbed particles from the surface of the nickel foam substrate. After acetone ultrasonic cleaning, the nickel foam substrate is dried in an oven at 40°C to 80°C, and then cut to a predetermined electrode length and width to obtain a nickel foam current collector.
[0019] Secondly, prepare the positive electrode slurry.
[0020] Nickel hydroxide, yttrium oxide, and cobalt hydroxide were weighed and dry-mixed at a mass ratio of 9.9:0.01:0.09 to obtain a nickel-containing cathode mixed powder. Polyvinylidene fluoride (PVDF) was separately added to N-methylpyrrolidone to prepare a 5% to 15% PVDF solution. The nickel-containing cathode mixed powder, conductive agent, and PVDF solution were added to a stirring container. The mixture was first wetted at a low speed, then the stirring speed was increased to disperse the powder, ensuring it was wetted by the PVDF solution and formed a uniform slurry. After dispersion, vacuum degassing was performed to obtain the cathode slurry. As a specific example, the nickel-containing cathode mixed powder and PVDF were prepared at a mass ratio of approximately 90:10, with the PVDF added in solution form. The conductive agent was selected from one or more of nickel powder, acetylene black, graphite powder, and cobalt hydroxide.
[0021] Next, apply the coating using a scraper.
[0022] The pretreated nickel foam current collector is spread evenly on the doctor blade coating station, keeping it in an expanded state. The positive electrode slurry is placed at one end of the nickel foam current collector. The gap between the doctor blade and the nickel foam current collector is adjusted, and the doctor blade moves along the surface of the nickel foam current collector. During the doctor blade movement, the positive electrode slurry enters the pores of the nickel foam current collector under the combined action of doctor blade pressure and adsorption through the pores of the nickel foam, forming a wet film on the surface of the nickel foam current collector. The thickness of the wet film coated by the doctor blade is controlled between 10 μm and 200 μm, and the linear speed of the doctor blade coating is controlled between 0.3 m / min and 1.5 m / min; under a specific condition in this embodiment, the wet film thickness is 150 μm.
[0023] Then, multi-stage drying is carried out.
[0024] The coated electrode sheet is laid flat in a forced-air drying oven and dried for 2 to 3 hours at 70°C to 90°C, followed by a second stage of drying at 90°C to 110°C for 2 to 3 hours. The drying air velocity is controlled at 0.1 m / s to 1 m / s. After the first stage of drying, most of the solvent in the coated electrode sheet is removed; after the second stage of drying, the polyvinylidene fluoride bonding system is set, resulting in a dried electrode sheet.
[0025] Finally, the material is rolled and cut.
[0026] The dried electrode sheet is fed into a rolling mill for pressing, and the thickness of the pressed electrode sheet is controlled between 0.65 mm and 0.85 mm. The pressed electrode sheet is then cut according to the electrode assembly dimensions to obtain the nickel hydroxide electrode. The nickel hydroxide electrode prepared using the above process has an active material surface loading of 110 mg / cm³. 2The structure of the nickel hydroxide electrode prepared in this embodiment is as follows: the pores of the nickel foam current collector are filled with a positive electrode material formed by nickel hydroxide, yttrium oxide, cobalt hydroxide, conductive agent and polyvinylidene fluoride. The surface of the nickel foam current collector retains a positive electrode material layer formed after the thickness is limited by a scraper. The positive electrode material layer and the nickel foam current collector are combined into an integral electrode sheet through multi-stage drying and rolling.
[0027] For performance testing, the nickel hydroxide electrode prepared using the method described in this embodiment was assembled into a three-electrode test system for capacity testing. This system used the prepared nickel hydroxide electrode as the working electrode, a high-purity platinum sheet as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. The electrolyte was a mixed solution of 6 mol / L potassium hydroxide and 15 g / L lithium hydroxide. During cycle testing, the electrode was first charged at a 0.2C rate for 5.5 h, and then discharged at a constant current of 0.2C to a cutoff voltage of 0.0 V relative to the mercury / mercury oxide reference electrode. The test results showed that the electrode's specific capacity reached 215 mAh / g, and the coulombic efficiency remained stable above 98%.
[0028] Figure 1 The cyclic voltammetry curves of the electrode prepared in Example 1 are shown. Figure 2 The charge-discharge curves of the electrode prepared in Example 1 are shown. Figure 1 It can be seen that the electrode exhibits a significant redox response within the test potential range; by Figure 2 It can be seen that the discharge specific capacity remained at a high level in the first three cycles, indicating that the prepared electrode has a relatively stable charge-discharge curve. Therefore, this embodiment demonstrates that the combination of nickel foam pretreatment, slurry preparation, doctor blade coating, multi-stage drying, and rolling enables the nickel hydroxide electrode to achieve a high areal loading, high specific capacity, and stable charge-discharge performance.
[0029] It should be understood that numerous specific implementation decisions can be made during the development of any practical implementation, such as in any engineering or design project. Such development efforts may be complex and time-consuming, but for those skilled in the art who benefit from this disclosure, the development effort will be a routine work of design, manufacturing, and production without requiring much experimentation.
[0030] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a nickel hydroxide electrode by blade coating, characterized in that, include: The nickel foam substrate is subjected to surface pretreatment, drying and cutting in sequence to obtain the nickel foam current collector; A nickel-containing positive electrode mixed powder, a conductive agent, polyvinylidene fluoride, and N-methylpyrrolidone are mixed, dispersed by stirring, and degassed to obtain a positive electrode slurry. The nickel-containing positive electrode mixed powder includes nickel hydroxide, yttrium oxide, and a cobalt source compound. The nickel foam current collector is laid flat and fixed. The positive electrode slurry is placed at one end of the nickel foam current collector, and a scraper is used to move along the surface of the nickel foam current collector to allow the positive electrode slurry to enter the pores of the nickel foam current collector and form a wet film on the surface of the nickel foam current collector to obtain a coated electrode sheet. The coated electrode sheet is subjected to a first stage of drying and a second stage of drying to obtain a dried electrode sheet. The temperature of the first stage of drying is 70°C to 90°C, and the temperature of the second stage of drying is 90°C to 110°C. The dried electrode sheet is rolled and cut to obtain the nickel hydroxide electrode.
2. The method for preparing a nickel hydroxide electrode by blade coating according to claim 1, characterized in that, The surface pretreatment includes ultrasonic cleaning of the nickel foam substrate in a citric acid solution, and then ultrasonic cleaning of the nickel foam substrate in acetone.
3. The method for preparing a nickel hydroxide electrode by blade coating according to claim 2, characterized in that, The nickel foam substrate is ultrasonically cleaned in citric acid solution and then washed with water. The nickel foam substrate is ultrasonically cleaned in acetone and then dried at 40°C to 80°C.
4. The method for preparing a nickel hydroxide electrode by blade coating according to claim 1, characterized in that, The thickness of the nickel foam substrate is 1 mm, and the number of pores in the nickel foam substrate is 110 PPI.
5. The method for preparing a nickel hydroxide electrode by blade coating according to claim 1, characterized in that, The nickel hydroxide, the yttrium oxide, and the cobalt source compound are mixed in a mass ratio of 9.7 to 9.9: 0.01 to 0.04: 0.05 to 0.09 to form the nickel-containing cathode mixed powder, wherein the cobalt source compound is cobalt oxide or cobalt hydroxide.
6. The method for preparing a nickel hydroxide electrode by blade coating according to claim 1, characterized in that, Based on 100 parts by weight of the nickel-containing cathode mixed powder, the conductive agent is 0.01 to 5 parts by weight, and the polyvinylidene fluoride is 8 to 20 parts by weight.
7. The method for preparing a nickel hydroxide electrode by blade coating according to claim 1 or 6, characterized in that, The conductive agent is selected from one or more of nickel powder, acetylene black, graphite powder and cobalt hydroxide; the polyvinylidene fluoride is added as a polyvinylidene fluoride solution, the mass fraction of the polyvinylidene fluoride solution is 5% to 15%, and the solvent of the polyvinylidene fluoride solution is N-methylpyrrolidone.
8. The method for preparing a nickel hydroxide electrode by blade coating according to claim 1, characterized in that, The thickness of the wet film coated by the doctor blade is from 10 μm to 200 μm, and the linear speed of the doctor blade coating is from 0.3 m / min to 1.5 m / min.
9. The method for preparing a nickel hydroxide electrode by blade coating according to claim 8, characterized in that, The thickness of the wet film coated by the doctor blade is 150 μm, and the gap between the doctor blade and the nickel foam current collector during the doctor blade coating process is set according to the thickness of the wet film.
10. The method for preparing a nickel hydroxide electrode by blade coating according to claim 1, characterized in that, The drying time for the first stage is 2 to 3 hours, the drying time for the second stage is 2 to 3 hours, and the drying wind speed is 0.1 m / s to 1 m / s; the thickness of the rolled electrode sheet is 0.65 mm to 0.85 mm.